DNA Methyltransferase Inhibition Promotes Th1 Polarization in Human CD4+CD25high FOXP3+ Regulatory T Cells but Does Not Affect Their Suppressive Capacity - Sija Landman; Marjan Cruijsen; Paulo C. M. Urbano; Gerwin Huls; Piet E. J. van Erp; Esther van Rijssen; Irma Joosten; Hans J. P. M. Koenen (Journal of Immunology Research)
Regulatory T cells (Treg) can show plasticity whereby FOXP3 expression, the master transcription factor for Treg suppressor function, is lost and proinflammatory cytokines are produced. Optimal FOXP3 expression strongly depends on hypomethylation of the FOXP3 gene. 5-Azacytidine (Aza) and its derivative 5-aza-2′-deoxycytidine (DAC) are DNA methyltransferase inhibitors (DNMTi) that are therapeutically used in hematological malignancies, which might be an attractive strategy to promote Treg stability. Previous in vitro research primarily focused on Treg induction by DAC from naïve conventional CD4+ T cells (Tconv). Here, we examined the in vitro effect of DAC on the stability and function of FACS-sorted human naturally occurring CD4+CD25high FOXP3+ Treg. We found that in vitro activation of Treg in the presence of DAC led to a significant inhibition of Treg proliferation, but not of Tconv. Although Treg activation in the presence of DAC led to increased IFNγ expression and induction of a Thelper-1 phenotype, the Treg maintained their suppressive capacity. DAC also induced a trend towards increased IL-10 expression. In vivo studies in patients with hematological malignancies that were treated with 5-azacytidine (Vidaza) supported the in vitro findings. In conclusion, despite its potential to increase IFNγ expression, DAC does preserve the suppressor phenotype of naturally occurring Treg.